PERBEDAAN MODEL KANDANG LITTER DAN RAK PADA SISTEM KANDANG CLOSE HOUSE TERHADAP PERFORMAN AYAM BROILER DI EGI FARM KABUPATEN BLITAR - Saputra, Fani Andika Saputra; Esti, Risma Novela; Rahmawati, Resti Yuliana (AVES: Jurnal Ilmu Peternakan, 2024)
The structure of the cage system is one of the factors determining the comfort of broiler chickens when reared. So it is necessary to pay attention to the cage model that is built appropriately to obtain optimal broiler chicken performance. This research aims to test and analyze the effectiveness of the performance of broiler chickens kept in rack and litter cage models. This research was carried out at Egi Farm, Blitar Regency, using 2 different cage models, namely rack and litter cage models. Data were analyzed using the Independent samples T-test. The parameters taken in this study were feed consumtion, body weight gain (PBB), feed conversion ratio (FCR), and mortality. The research results showed that the use of 2 different cage models, namely the rack and litter cage models, had an influence on feed consumption, body weight gain, feed conversion and mortality. The rack cage model obtained better chicken performance results with an average value of feed consumption during rearing of 1072.67 grams/head, a body weight gain value of 56.59 grams/head and an FCR value of 1.39. Meanwhile, litter cages had an average feed consumption value of 1017.45 grams/head, body weight gain of 50.67 grams/head and FCR value of 1.47. The rack cage model has a lower mortality rate than the litter cage model. Broiler chickens reared in rack style cages performed better compared to litter model cages